2016
DOI: 10.1007/s10557-016-6700-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-Oleic Acid Prevents Hypoxia- and Asymmetric Dimethylarginine-Induced Pulmonary Endothelial Dysfunction

Abstract: Rationale Pulmonary hypertension (PH) represents a serious health complication accompanied with hypoxic conditions, elevated levels of asymmetric dimethylarginine (ADMA), and overall dysfunction of pulmonary vascular endothelium. Since the prevention strategies for treatment of PH remain largely unknown, our study aimed to explore the effect of nitro-oleic acid (OA-NO2), an exemplary nitro-fatty acid (NO2-FA), in human pulmonary artery endothelial cells (HPAEC) under the influence of hypoxia or ADMA. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Several work in the literature demonstrate the pluripotent activity of NO 2 -FA, some of them related to NO 2 -OA ( Kelley et al, 2008 ; Liu et al, 2008 , 2013 ; Kansanen et al, 2009 ; Wang et al, 2010a , b ; Sculptoreanu et al, 2010 ; Artim et al, 2011 ; Klinke et al, 2014 ; Zhang et al, 2014 ; Ambrozova et al, 2016 ; Koudelka et al, 2016 ). It has been demonstrated their capacity to modulate inflammatory processes, e.g., induction of HO-1 ( Ferreira et al, 2009 ; Kansanen et al, 2011 , 2012 ; Diaz-Amarilla et al, 2016 ) or reduction of pro-inflammatory mediators by inhibiting enzyme activities, e.g., inhibition of 5-LOX in neutrophils ( Awwad et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several work in the literature demonstrate the pluripotent activity of NO 2 -FA, some of them related to NO 2 -OA ( Kelley et al, 2008 ; Liu et al, 2008 , 2013 ; Kansanen et al, 2009 ; Wang et al, 2010a , b ; Sculptoreanu et al, 2010 ; Artim et al, 2011 ; Klinke et al, 2014 ; Zhang et al, 2014 ; Ambrozova et al, 2016 ; Koudelka et al, 2016 ). It has been demonstrated their capacity to modulate inflammatory processes, e.g., induction of HO-1 ( Ferreira et al, 2009 ; Kansanen et al, 2011 , 2012 ; Diaz-Amarilla et al, 2016 ) or reduction of pro-inflammatory mediators by inhibiting enzyme activities, e.g., inhibition of 5-LOX in neutrophils ( Awwad et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…4, C and D), especially the pathways related to the response to hypoxia, fluid shear stress, and to atherosclerosis. In ECs, NO 2 -FAs enhance NO bioavailability (29,31), inhibit inflammation (21,57) and oxidative inflammatory reactions (19,25,27,29,67), enhance the heat shock response (25), and promote angiogenesis (45). NO 2 -OA and NO 2 -LA inhibit NF-B activation and TNF-␣-stimulated proinflamma-tory cytokine expression (10,21).…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 Hypoxia leads to a decrease in the expression of eNOS in vascular ECs. 37 , 38 However, several studies have indicated that the gene expression, protein content, and activity of lung eNOS are high in mice with chronic hypoxic PH. 39 41 These findings are consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%